The International Criminal Tribunal for the Former Yugoslavia: An analysis of the legal basis for its operation. - Khan, Ausma Zehanat. (University of Ottawa (Canada), 1996)
The premise of this thesis is that the creation of the international Criminal Tribunal for the Former Yugoslavia is a unique initiative aimed at reasserting the perspective of the international community on what type of conduct is considered acceptable and legal in international and internal warfare. The foremost question that must be asked by anyone studying the tribunal is what is it meant to achieve? In my analysis, I focus on three primary issues: (1) what is the legal basis for the operation of the ICTFY? This involves looking both at the law that empowers the tribunal, as well as the laws that the tribunal will rely on in interpreting and prosecuting genocide, war crimes and crimes against humanity. (2) Should the ICTFY be regarded as a mechanism aimed at ending the conflict on the ground, and is this, in fact, a role that tribunals, domestic or international, are supposed to play; and (3) if so, is the ICTFY a successful resolution mechanism? The third question will be answered in the negative. (Abstract shortened by UMI.)
Keywords: Political Science, International Law and Relations.